2003
DOI: 10.1001/archopht.121.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Increased Detection Rate of Glaucomatous Visual Field Damage With Locally Condensed Grids

Abstract: To compare detection rates of glaucomatous visual field defects (VFDs) between the conventional 6°ϫ 6°stimulus grid and locally condensed target arrangements in morphologically suspicious regions. Methods: A total of 66 eyes of 66 patients with glaucoma or patients suspected of having glaucoma (34 females and 32 males; age range, 14-85 years) were enrolled in this study. Individual, local target condensation was realized by fundus-oriented perimetry (FOP) using a campimeter and compared with the results of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 26 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…15C shows the same results after scaling and rotating to bring the disc centers into register. Although some inter-individual variation remains, scaling and rotating, as suggested previously (Schiefer et al, 2003; Jansonius et al, 2009), brought the RNFL bundle tracings approximately into agreement.…”
Section: Individual Differences and The Position Of The Optic Discsupporting
confidence: 74%
See 1 more Smart Citation
“…15C shows the same results after scaling and rotating to bring the disc centers into register. Although some inter-individual variation remains, scaling and rotating, as suggested previously (Schiefer et al, 2003; Jansonius et al, 2009), brought the RNFL bundle tracings approximately into agreement.…”
Section: Individual Differences and The Position Of The Optic Discsupporting
confidence: 74%
“…Jansonius et al (2009) substantially reduced individual differences in RNFL bundle projections by rotating and scaling the fundus images so that the centers of the fovea and disc were aligned (Schiefer et al, 2003). To confirm this scaling assumption, 9 fundus photos were selected by Dr. Randy Kardon at the University of Iowa from a large set based upon the clarity of the fiber bundles (Nguyen et al ARVO, 2012 abstract).…”
Section: Individual Differences and The Position Of The Optic Discmentioning
confidence: 99%
“…Based in part on our findings in monkey imaging (Strouthidis et al, 2009a), and also on the same studies of RNFL anatomy and its relationship to structure-function correlation mentioned previously (Garway-Heath et al, 2000; Harwerth et al, 2010; Hood and Kardon, 2007; Jansonius et al, 2009; Jonas et al, 1989; Patel et al, 2012; Schiefer et al, 2003; Turpin et al, 2009), we have suggested (Burgoyne, 2015b; Chauhan and Burgoyne, 2013) that OCT data sets of the ONH, RNFL and macula should not only be regionalized relative to the FoBMO axis, but OCT data acquisition should be organized relative to it as well. Figures 43–47 illustrate our strategy for OCT phenotyping the ONH, RNFL and Macula of the monkey (and human) (Burgoyne, 2015a) eye.…”
Section: 0 Next Steps and New Directionsmentioning
confidence: 53%
“…The logic for using the FoBMO axis to regionalize ONH, RNFL, and macular anatomy has been suggested by previous studies of RNFL anatomy and its relationship to structure-function correlation (Garway-Heath et al, 2000; Harwerth et al, 2010; Hood and Kardon, 2007; Jansonius et al, 2009; Jonas et al, 1989; Patel et al, 2012; Schiefer et al, 2003; Turpin et al, 2009). As per our 2015 publication describing our LMA method (Lockwood et al, 2015), we estimate the location of the FoBMO axis relative to the vertical and horizontal axes of the embedded 3D HMRN so as to impose a consistent grid of twelve 30° sectors on the 3D HMRN LC anatomy of each eye (Figure 40).…”
Section: 0 Next Steps and New Directionsmentioning
confidence: 99%
“…Initial studies of the angle and distance between the fovea and the center of the ONH have been based on the clinical disc margin within a clinical photograph [19], [30], [31], or SLO reflectance image [5], [9], [32]. Patel et al[14] used the SDOCT-determined neural canal opening [33][35] (previous terminology that is equivalent to BMO) and fovea to co-localize RNFLT measurements from two different SDOCT instruments.…”
Section: Discussionmentioning
confidence: 99%